Trade policy substitution: Theory and evidence from Specific Trade Concerns - Cosimo Beverelli; Mauro Boffa; Alexander Keck (World Trade Organization (WTO), 2014)
We investigate to what extent the probability that a Specific Trade Concern (STC) is raised in the WTO against a Member in a given sector is affected by past reductions in applied tariffs. Employing an identification strategy based on 'new measures', we find evidence of a substitution of non-tariff measures for tariffs both in the sample of TBT and in the sample of SPS concerns. While in the SPS sample this result holds both among developed and developing economies, in the TBT sample such 'trade policy substitution' only occurs when the country maintaining the measure at issue is economically developed. These results are consistent with our theoretical model, which predicts policy substitution between tariffs and standards in economies where meeting such standards is relatively less costly and in sectors where meeting such standards is relatively more important from the perspective of producers.
Keywords: F13; F14; F15; 330; Import; International Trade Agreements; Non Tariff; Tariff; WTO